Some Aspects of the Biology and Control of Vascular Streak Dieback Pathogen (Oncobasidium Theobromae) of Cocoa - Lam, Chin Hee (1988)
Vascular streak dieback (VSD) caused by Oncobasidiun theobromae Talbot and Keane is presently the most threatening disease of cocoa in Malaysia and the Southeast Asia regions. Studies were undertaken on aspects of the biology and control of the fungus. Solid Corticiurn culture medium (CCM) and liquid coconut water medium which were modified had provided better growth and prolonged survivability of 0. theobrornae. Nutritional factors viz. nitrogen, carbon and vitamin sources were observed to improve the growth of the fungus on these media.